Frequent Ongoing T-Cell Receptor Rearrangements in Childhood B-Precursor Acute Lymphoblastic Leukemia: Implications for Monitoring Minimal Residual Disease - Steenbergen, Eric J.; Verhagen, Onno J.H.M.; Leeuwen, Eleonore F. van; Berg, Henk van den; Borne, Albert E.G.Kr. von dem; Schoot, C.Ellen van der (Blood, 1995)
Crosslineage T-cell receptor δ (TCRδ) rearrangements are widely used as tumor markers for the follow up of minimal residual disease in childhood B-precursor acute lymphoblastic leukemia (ALL) by polymerase chain reaction (PCR). The major drawback of this approach is the risk of false-negative results due to clonal evolution. We investigated the stability of Vδ2Dδ3 rearrangements in a group of 56 childhood El-precursor ALL patients by PCR and Southern blot analysis. At the PCR level, VS2Dδ3-to-Jα rearranged subclones (one pathway for secondary TCRδ recombination) were demonstrated in 85.2% of Vδ2Dδ3-positive patients tested, which showed that small subclones are present in the large majority of patients despite apparently monoclonal TCRδ Southern blot patterns. Sequence analysis of Vδ2Dδ3Jα rearrangements showed a biased Jα gene usage, with HAP05 and JαF in 26 of 32 and 6 of 32 clones, respectively. Comparison of Vδ2Dδ3 rearrangement status between diagnosis and first relapse showed differences in seven of eight patients studied. In contrast, from first relapse onward, no clonal changes were observed in six patients studied. To investigate the occurrence of crosslineage TCRδ rearrangements in normal B and T cells, fluorescence-activated cell sorter-sorted peripheral blood CD19+/CD3– and CD19–/CD3+ cell populations from three healthy donors were analyzed. Vδ2Dδ3 rearrangements were detected at low frequencies in both B and T cells, which suggests that Vδ2-to-Dδ3 joining also occurs during normal B-cell differentiation. A model for crosslineage TCRδ rearrangements in B-precursor ALL is deduced that explains the observed clonal changes between diagnosis and relapse and is compatible with multistep leukemogenesis of B-precursor ALL.